Reconsidering the Closed Proportional System for Indonesia - Rahani Itsia Kurnianingrum (Universitas Medan Area, 2020)
This paper explains how the application of an open proportional system and a closed proportional system in the legislative elections in Indonesia. The problem is focused on how the consequences of implementing an open proportional system compared to closed proportionality after the widespread discourse to return to a closed proportional system. Moreover, a number of problems emerged after the 2019 simultaneous elections were carried out in an open proportional system. The open proportional system was considered more complicated for voters and for election administrators. Meanwhile, for election participants, an open proportional system created internal conflicts in political parties. The data in this paper were collected through literature study and analyzed qualitatively. This study concludes that a closed proportional system was considered to be more efficient in the process of casting and printing the ballots. The closed proportional system was also simple for voters, because voters only chose images of political parties. On the other hand, political parties as election participants must also improve their party system to be more democratic so that the cadres of the best political parties who side with the people have the same opportunity to compete in the election. Ease of voters and the quality of election participants are important because the essence of elections is participation and contestation.